(untitled) (Revista Brasileira Multidisciplinar, 2025)
The collection and analysis of data through technological prospecting of patents has been used as a support for the creation and improvement of new technologies such as Arduino applied to food. One way to test equipment in processes is through the use of microcontrollers, such as Arduino, which allows the use of control tools to perform small-scale automation. Arduino is a tool that can be used for various functions and activities, even being used as a patent record. The objective of this study was to carry out a technological monitoring of patents on Arduino applications in the food sector. After conducting a preliminary patent search in various databases, including Lens, DERWENT, Espacenet, and INPI, patents from a comprehensive database were selected to perform technological monitoring on the application of Arduino in food. It was found that, from the most comprehensive database, DERWENT, with 72 patents, all of which correspond to the engineering field, the main global competitors in the development and protection of Arduino-related technologies in food are countries like India, mainly Chandigarh University and Lovely Professional, which invest in stimulating innovation. As evaluated in INPI data, in Brazil, there is little technological advancement aimed at Arduino applications, presenting only 2 registered patents. However, advancements in inventions related to this technology have grown at a moderate pace. Overall, the developed indicators suggest that patent development in this area has specific growth potential.